2020
DOI: 10.1371/journal.pbio.3000821
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of antigen-specific, disulphide-rich knob domain peptides from bovine antibodies

Abstract: As a novel alternative to established surface display or combinatorial chemistry approaches for the discovery of therapeutic peptides, we present a method for the isolation of small, cysteine-rich domains from bovine antibody ultralong complementarity-determining regions (CDRs). We show for the first time that isolated bovine antibody knob domains can function as autonomous entities by binding antigen outside the confines of the antibody scaffold. This yields antibody fragments so small as to be considered pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 47 publications
5
66
0
Order By: Relevance
“…Using this approach, we obtained four knob domain peptides: K8, K57, K92, and K149, which we have shown to display tight binding to human C5. Previously we reported equilibrium dissociation constants of 17.8 nM for K8, 1.4 nM for K57, <0.6 nM for K92, and 15.5 nM for K149 ( Macpherson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Using this approach, we obtained four knob domain peptides: K8, K57, K92, and K149, which we have shown to display tight binding to human C5. Previously we reported equilibrium dissociation constants of 17.8 nM for K8, 1.4 nM for K57, <0.6 nM for K92, and 15.5 nM for K149 ( Macpherson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 89%
“…By the end of 2019, over 60 peptide drugs have received regulatory approval, with an estimated 400 more in active development globally ( Lau and Dunn, 2018 ; Lee et al, 2019 ). As a potential route to discover therapeutic peptides, we previously reported a method for deriving peptides from the ultra-long heavy chain complementarity determining region 3 (ul-CDRH3), which are unique to a subset of bovine antibodies ( Macpherson et al, 2020 ). We have shown that knob domains, a cysteine-rich mini-domain common to all ul-CDRH3, can bind antigen autonomously when removed from the antibody scaffold ( Macpherson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations